The Effect of Picture Cued Task on Students’ Speaking Ability - Safira, Tia; Gushendra, Rizky (Journal of English and Arabic Language Teaching, 2024)
This research aim to find out whether there is significant different between students’ speaking ability before using picture cued and after using picture cued at eighth grade students’ of Junior High School Muhammadiyah Tebing Tinggi. In this research the researcher used pre - experimental design one group pre-test and post-test. The population of this research was all of the students at class VIII Junior High School Muhammadiyah Tebing Tinggi. The sample for the research was took 15 students. The data analysis in this research is using t-test. In analyzing the data, the researcher will use paired sample t-test formula. The result of this research shown that the pre-test score calculated as 67% was at “Enough” level and the post-test score calculated as 67% was at “Good” level. The result calculation of the test shown that sig. (2-tailed) showed 0.000. Based on the data, if the value of sig. (2- tailed) is less than 0.05 Ha will be accepted. The researcher concludes that there is a significant different between students’ speaking ability before using picture cued and after using picture cued to improve students’ speaking ability at eighth grade students’ of Junior High School Muhammadiyah Tebing Tinggi.